Professional Development Barriers of Teachers: Qualitative Research - Soleh, Mokhamad; Rokhman, Fathur; Mahmud, Amir (Universitas Negeri Semarang, 2025)
Teacher professional development (PD) is widely recognized as a key factor in enhancing teaching quality and improving student learning outcomes. However, teachers often face significant barriers to accessing and engaging in PD, which operate at individual, institutional, and systemic levels. This study employs a Systematic Literature Review (SLR) of 25 qualitative and mixed-methods studies published between 2010 and 2024 to identify and analyze these barriers. Thematic analysis reveals five major challenges: time constraints and heavy workloads, limited access and infrastructure (especially in remote areas), misalignment between PD content and classroom needs, lack of leadership and policy support, and low teacher motivation and professional identity. These barriers are categorized across three levels: individual (e.g., burnout, lack of motivation), institutional (e.g., inadequate school leadership, absence of collaborative structures), and systemic (e.g., digital divide, centralized and non-contextual policy design). The review also synthesizes key recommendations from the literature, including the need for contextually relevant PD, collaborative models such as Professional Learning Communities (PLCs), stronger instructional leadership, and inclusive, long-term policy frameworks. Findings highlight the importance of moving beyond superficial training models toward a systemic, multi-layered approach that fosters a sustainable culture of professional learning and empowers teachers as active agents of educational change.